The Star Alphabet by E.L.T. Mesens : Dade & Surrealism in Brussels, Paris & London. - van den Bossche, Phillip; Weiss, Erich; Clissen, Anouck; Mels, Mieke; Mu.Zee, Oostende (Oostende : Mu.ZEE, 2013)
Mesens, E.L.T ; Schwitters, Kurt ; Picabia, Francis ; P-G Van Hecke, Albert ; Kessels, Willy ; Thiry, Georges ; Kar, Ida ; Ray, Man ; Magritte, René ; Toorop, Charley ; et al.
Mu.ZEE, Kunstmuseum aan Zee, Oostende, July 6 - November 17, 2013
kunstcatalogus